To apply the Zero Power Rule, we need to acknowledge that any non-zero number raised to the power of zero is equal to 1. Therefore:
-
For the term \((-33)^0\): \((-33)^0 = 1\)
-
For the term \(27^0\): \(27^0 = 1\)
Now substituting these values into the expression \(9*(-33)^0 + \frac{3}{2}(8 - 27^0)\):
-
Substitute \((-33)^0\) with \(1\): \[ 9*(-33)^0 = 9*1 = 9 \]
-
Substitute \(27^0\) with \(1\): \[ 8 - 27^0 = 8 - 1 = 7 \]
Now, we can simplify the entire expression: \[ 9*(-33)^0 + \frac{3}{2}(8 - 27^0) = 9 + \frac{3}{2}(7) \]
Now, let's express it in the requested format: \[ 9 \cdot 1 + \frac{3}{2} \cdot (8 - 1) \Rightarrow 9 \cdot 1 + \frac{3}{2} \cdot 7 \]
Thus, the expression can be represented as: \[ 9*(1) + \frac{3}{2}(8-1) \]
So, filling in the blanks: \[ \boxed{9*1 + \frac{3}{2}(8-1)} \]